The influence of habitat heterogeneity and disturbance on benthic community structure in deep-sea polymetallic nodule environments and management implications for seabed mining - Ullmann, Ailish; Rowden, Ashley A.; Leduc, Daniel; Zeppilli, Daniela (Frontiers in Marine Science, 2025)
Habitat heterogeneity is known to influence faunal community structure, but its influence on deep-sea benthic communities remains understudied, particularly for polymetallic nodule environments in abyssal waters. As nodules are currently of interest for mining, understanding the potential impact of this disturbance on habitat heterogeneity, and the subsequent effect on faunal communities, becomes critical for developing environmental management plans. Although some aspects of the influence of habitat heterogeneity on the nodule-associated fauna have been studied, the influence on multiple size components of the benthic community across varying spatial scales has not yet been fully assessed, and the current metrics by which habitat heterogeneity is measured may be insufficient. This review synthesizes existing research regarding habitat heterogeneity, the influence of disturbance on habitat heterogeneity, and the influence of this heterogeneity on metazoan fauna (megafauna, macrofauna, and meiofauna) in polymetallic nodule environments across spatial scales. Current gaps in knowledge and the implications of this knowledge for the management of proposed deep-seabed mining are also discussed.